1088 Heart Rate Variability During Sleep in Adults With and Without a History of Depression and the Influence of Antidepressant Use. (27th May 2020) - Egeler, M E; Bowman, M; Thayer, J F; Brindle, R C; Hall, M; Kline, C E
Abstract: Introduction: Individuals with depression have an increased risk for cardiovascular disease. While lower daytime HRV may be one mechanism of this association, it is less clear whether HRV during sleep (sHRV) differs between adults with and without depression. Examining sHRV is an important measure to test given evidence that nocturnal differences in physiology are strong predictors of cardiovascular disease. Methods: 118 adults who completed psychiatric interviews between the ages of 21-60 y (T1) returned 18.7 ± 4.5 years later for a re-evaluation of their mental health and assessment of sleep (T2). 71 participants were diagnosed with Major Depressive Disorder (MDD) at either T1 or T2, while 47 participants were free from depression at both time points. At T2, participants underwent an overnight polysomnogram with concurrent assessment of electrocardiography. The primary measures of sHRV were root mean square of successive differences (RMSSD) values during rapid eye movement (REM) sleep and non-REM (NREM) sleep stages N2 and N3. Lower values of RMSSD suggest lower parasympathetic activity. RMSSD values were natural log-transformed prior to analysis. Differences in RMSSD between depressive groups were examined using analysis of covariance (ANCOVA), adjusting for age, body mass index, gender, race, and antihypertensive medication use. Additional ANCOVA models adjusted for antidepressant use. Results: Participants with current or a history of MDD had lower RMSSD values during REM sleep (P=.01) and a trend toward lower values during NREM (P=.06) compared to those without MDD. Antidepressant use was significantly associated with lower RMSSD during both REM (P=.002) and NREM sleep (P<.001). Depression history was no longer associated with RMSSD during NREM or REM sleep following adjustment for antidepressant use (P>.40). Conclusion: These data indicate that adults with MDD exhibit lower parasympathetic activity during sleep compared to those without MDD. These associations were modified by antidepressant use, suggesting that antidepressants may partially explain the association between depression and sHRV. Future studies investigating the influence of specific antidepressants for modifying nocturnal physiology may help to better understand the link between depression and cardiovascular disease risk. Support: This study was funded by National Institutes of Health (NIH) grants R01 HL104607 and K23 HL118318.